Regional activation of supraspinatus and infraspinatus sub-regions during dynamic tasks performed with free weights - Calver, R.; Alenabi, T.; Cudlip, A.; Dickerson, C. R.; Mondal, P.; Kim, S. Y. (Journal of Electromyography and Kinesiology, 2022)
Growing evidence supports the existence of distinct anatomical sub-regions within supraspinatus and infraspinatus, but only recently has attention turned to exploring their potential functional differences. Using indwelling fine-wire electromyography, muscle activity was investigated from these sub-regions in 15 participants (mean 34yr, 170cm, 71.9kg) during dynamic external rotation (ER), abduction, flexion, and scaption tasks with and without free weights corresponding to 50% and 75% of the participant`s five repetition maximum. Electromyography data were normalized to isometric and isokinetic maximal voluntary contractions and activation ratios for each sub-region compared.